2019
DOI: 10.3127/ajis.v23i0.1759
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supervisors’ Perceived Communication Style on Subordinate’s Psychological Capital and Cyberloafing

Abstract: Drawing from Conservation of Resources Theory (COR), the purpose of this paper is to examine the impact of supervisor’s perceived communication style (passive, aggressive, and assertive styles) on subordinates PsyCap and cyberloafing. The study also tests the mediating role of PsyCap in the relationship between perceived communication style (CS) of supervisor and cyberloafing. In total, 680 full-time managerial employees from seven diverse firms in India were studied through questionnaire survey. Standard inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
0
13
0
1
Order By: Relevance
“…In recent years, cyberloafing, a form of deviant workplace behavior, has attracted attention of practitioners and academicians (Agarwal, 2019;Lim, 2002). Cyberloafing is defined as any "voluntary act of employees" using their companies' internet access during office hours to surf non-job-related websites for personal purposes and to check (including receiving and sending) personal e-mail (Lim, 2002, p. 677).…”
mentioning
confidence: 99%
“…In recent years, cyberloafing, a form of deviant workplace behavior, has attracted attention of practitioners and academicians (Agarwal, 2019;Lim, 2002). Cyberloafing is defined as any "voluntary act of employees" using their companies' internet access during office hours to surf non-job-related websites for personal purposes and to check (including receiving and sending) personal e-mail (Lim, 2002, p. 677).…”
mentioning
confidence: 99%
“…Some scholars have used these terms interchangeably (Garrett & Danziger, 2008;Ugrin & Pearson, 2013;Vitak et al, 2011). Traditionally, PUTW literature often describes PUTW as employees' use of organisational IT resources for personal or nonwork-related purposes either at 1) the workplace or 2) during office time or business hours (Agarwal, 2019;B Cheng et al, 2020;Khansa et al, 2017;VKG. Lim, 2002).…”
Section: What Is Putw?mentioning
confidence: 99%
“…The convenience and invisibility may explain why PUTW is reported to be the main form of non-work-related behaviour at work (Ivarsson & Larsson, 2011). For example, recent studies have suggested that, on average, employees spend one to two hours every workday on PUTW (Kim, 2018), accounting for 10% to 30% of their work time (Agarwal, 2019;Askew et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cyberslacking has been hotly debated in the literature and a burning issue for more than two decades. Cyberslacking is the act of using the internet by an employee during working hours for personal gains (Agarwal, 2019;El Din & Baddar, 2019;Mamat & Baqutayan, 2019;Sze et al, 2019). Cyberslacking is a non-work-related engagement at the workplace which includes social networking, e-mailing, downloading, calling, texting, streaming, surfing, gaming, blogging, job hunting, gambling, billing, and booking (Dursun et al, 2018;Mamat & Baqutayan, 2019).…”
Section: Introductionmentioning
confidence: 99%